Rancang Bangun Sistem Informasi Nilai Berbasis Website Pada Sekolah Dasar Islam Azzahro Dengan Metode Waterfall - Choirul Azhari, Alfian; Pramana, Indra; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
The academic assessment process is one of the important aspects in the world of education, including at Azzahro Islamic Elementary School. However, the management of student grades carried out manually, either using paper or simple software such as spreadsheets, often faces various obstacles, such as the risk of errors in recording and calculating. To overcome these problems, this study aims to design and develop a Website-Based Grade Information System that can help manage grades more effectively, efficiently, and centrally. This study uses the Waterfall system development method, which consists of five main stages: needs analysis, system design, implementation, testing, and maintenance. The system developed allows for secure storage of student grade data, speeds up the grade processing process, reduces the risk of manual errors, and facilitates access and reporting by teachers or school administrators.